PENGGUNAAN MEDIA PEMBELAJARAN ALGODOO DALAM DISCOVERY LEARNING UNTUK MENINGKATKAN PENGUASAAN MATERI GERAK PARABOLA - Ainun Sarmilaz Burhan; Anatasija Limba; David Tuhurima (Science Map Journal, 2023)
This study aims to determine the increase in mastery of the material on the parabolic motion material for class X MA Negeri 1 Central Maluku which is taught using Algodoo media in the discovery learning model. This type of research is a descriptive study with a one group pretest-posttest research design, with 17 students as research samples obtained using the Random Sampling technique. The research data was collected through a written test and then analyzed descriptively. The results showed that the initial ability of students was in the failed qualification with an average value of 8.0, while the average score of the achievement of the final ability of students was 86.4 which was in good qualification. This is evidenced by the results of the N-gain test which shows the average value <g> students by 0.9 in high qualifications. Thus, it can be concluded that there is an increase in students' mastery of the material after being taught using the Algodoo learning media in the discovery learning model on the parabolic motion material for class X MA Negeri 1 Central Maluku